Cigarette smoking and adverse health outcomes in patients treated with maintenance dialysis. Issue 1 (31st October 2022) - Bek, Sibel G.; Marschner, Simone; Sud, Kamal; Johnson, David W.; Chow, Clara K.; Hawley, Carmel; Pilmore, Helen; Wong, Germaine; Lim, Wai; Lee, Vincent W.
Abstract: Background: The association of smoking with new‐onset cardiovascular disease, chronic lung disease, malignancy and mortality in dialysis is well‐known. The smoking prevalence and its association with clinical outcome was assessed. Methods: Multicentre cohort study using 'ANZDATA' Registry, 57 838 adults who commenced dialysis (>3 months) between 1990 and 2016 were included. Patients' demographics, initial dialysis modality, presence of comorbidities and smoking history are predictors. The primary outcome was all‐cause mortality. Secondary outcomes were smoking prevalence, cause‐specific mortality, non‐skin cancers, cardiovascular and chronic lung diseases. Results: Of the 57 838 patients, 56 512 (mean age of 58.9 ± 15.1 years, 40.1% female, 43% diabetic), had data on smoking history with 13.6% current, 40.7% former and 45.6% never smokers. Former and current smokers had 10% (HR 1.10; 95% CI: 1.08, 1.13) and 22%(HR 1.22; 95% CI: 1.18, 1.26) higher risk of all‐cause mortality. They were 13% (HR 1.13; 95% CI: 1.09, 1.18) and 23% (HR 1.23; 95% CI: 1.17, 1.29) for CVD mortality. Smoking was associated with higher mortality from respiratory failure (HR 1.59; 95% CI: 1.13, 2.23, p = .073 and HR 1.33; 95% CI: 1.01, 1.74, p = .042) for current and former smokers. Current and former smokers had higher risk for non‐skin cancer (HR 1.30; 95% CI: 1.19, 1.42 and HR 1.24; 95% CI: 1.17, 1.32). Smoking was associated with a higher rate of death from cancer (HR 1.26; 95% CI 1.19–1.33) and chronic lung disease (HR 1.48; 95% CI 1.15–1.92). Former and current smokers had a higher adjusted risk for de novo vascular disease (PVD, CVD), CAD (adjusted RR 1.1; 95% Cl: 1.09–1.12). Conclusions: In dialysis patients, smoking was associated with higher rates of all‐cause mortality, cardiovascular mortality, respiratory failure, chronic lung disease and malignancy along with higher risks of non‐skin cancers, de novo vascular disease and chronic lung disease. Summary at glance: Cigarette smoking is a very well‐known risk factor for mortality in dialysis patients. This is the first manuscript analysing hazardous effects of smoking by using the ANZDATA Registry. Besides well‐known negative impact on all‐cause mortality and chronic diseases, smoking trends in different age groups and time periods were reported in this study. This study underlines the negative impact of smoking in dialysis population. New guidelines and preventive measures should be designed according to different age groups.